Pengembangan Media Pembelajaran Matematika Berbasis Prezi Untuk Meningkatkan Minat Belajar Siswa - Dila Amanda; Sitti Inaya Masrura; Sartika Arifin (Pendidikan Matematika FKIP Universitas Mataram, 2023)
This study aims to developed and produced a Prezi-based mathematics learning media and to determined the validity, practicality and effectiveness of the learning media to increasing student interest in learning. The type of this study was Research and Development which refers to the ADDIE development model. The ADDIE. The results showed that the learning media was declared valid by the media expert validator with a total average of 3,62 and the material expert validator with a total average of 3,88. The learning media was declared practical judging by the positive and very positive responses givin by students and teacher, namely 83% and 89%. The learning media was declared effective because it was able to increase students’ learning interest seen from the increase in the average students’ learning interest before and sfter using the learning media from 46 to 62 and the result of the n-gain analysis of 0,60 which indicated an increase in students’ learning interest which was included in the “medium” category